Philosophy of Stem Cell Biology - Fagan, M. author. aut Link
XX, 274 p.
Keywords: This examination of stem cell biology from a philosophy of science perspective clarifies the field's central concept, the stem cell, as well as its aims, methods, models, explanations and evidential challenges. Relations to systems biology and clinical medicine are also discussed.